‘Bad Reputation’: Understanding General Reluctance to Voluntary Military Enlistment (Politeja, 2025)
This exploratory study investigates hesitation towards voluntary enlistment in the military. It seeks to understand the generic underlying factors that deter individuals from enlisting in the military at a time when conscription is less practiced in some countries. By using a qualitative method that involves Google Form and selected follow-up interviews, the findings in this work suggest that hesitancy towards voluntary enlistment in the military stems from a variety of factors that can be intrinsic, conditional/extrinsic, and partly institutional. It also highlights that reluctance to enlist voluntarily in the military is often influenced in some individuals by the behaviors of serving or ex-soldiers and is mediated by the soldiers themselves or by third party platforms.